Study on photocatalytic and mechanical properties of TiO2 modified pervious concrete - Linsong Wu; Mengjun Mei; Zhen Li; Shuhua Liu; Xingzhi Wang (Case Studies in Construction Materials, 2022)
Photocatalytic pervious concrete pavement is a potential and sustainable new method for treating urban air and water pollution, and there is now an increasing amount of research on TiO2 pervious concrete due to its excellent photocatalytic properties. In this study, pervious concrete with varying nano-TiO2 contents (0 %, 1 %, 2 %, 5 %, 8 %) was prepared and evaluated for its performance in purifying methyl orange (MO). The results show that as the TiO2 content increased from 0 % to 8 %, the photocatalytic degradation efficiency increased and then decreased, with the highest MO degradation rate of pervious concrete with 5 % TiO2 content was 42.8 % at 120 min. However, as the TiO2 content increases, the compressive strength and TiO2 utilization rate of pervious concrete gradually decrease, and the 28-day compressive strength decreases from 26.0 MPa to 13.5 MPa. Therefore, 2 % TiO2 content was determined to be optimal for pervious concrete.